POLA KOMUNIKASI SANTRI ETNIS MADURA YANG MENGALAMI CULTURE SHOCK DALAM INTERAKSI SOSIAL:: Studi Kasus Pondok Pesantren Raudlatul Muhsinin Kuwolu Bululawang Malang - Moh Amiruddin (Jurnal Penelitian Ilmiah INTAJ, 2020)
Communication is very important in everyday life. It is used to interact with others in social life. Without communication, it will be difficult to live a group and social life. Effective communication can be characterized by the meaning received by the communicant as the meaning of the message delivered by the communicator. Islamic boarding school is a traditional educational institution where the students are not only one ethnic but multi-ethnic including Madurese. In Raudlatul Muhsinin, a Salafiyah Islamic boarding school, located on the island of Java precisely in Malang Regency. So, the language used is Javanese. It is necessary to know the communication patterns used by students of Madureses who experienced culture shock. This research is conducted using qualitative data type that collected through observation and interviews. The result obtained is Madurese students use three communication patterns in interaction, including linear or one-way communication patterns, circular or two-way communication patterns and multi-way communication patterns.